An Agenda for Action - Bruhn, John G. author. aut Link
XVII, 243 p.
Keywords: A companion to the authors' Handbook of Clinical Sociology (Plenum Press, 1991), this pioneering text provides an introduction to this new field, covering its development, methods and tools, and illustrates the applications of sociological concepts to current social problems. Drs. Bruhn and Rebach present numerous examples to enable practitioners to apply their problem-solving skills. Key discussions address the values held by clients and practitioners and issues relating to sociological assessment and evaluation. This indispensable resource is enhanced by case illustrations, annotated bibliographies, and a glossary of terms.